Processing and Properties of Nanomaterials - Nur Aqilah, Makshut; Zainab, Ngaini (Springer, 2026)
Nanomaterials have garnered extensive interest due to their unique properties, which significantly differ from those of their bulk counterparts. This chapter explores the diverse methods employed in the production of nanomaterials, emphasising both top-down and bottom-up approaches. Top-down techniques, such as ball milling, lithography, sputtering, laser ablation and arc discharge, physically reduce the size of bulky materials to nano-sized particles. Conversely, bottom-up techniques, including chemical vapour deposition, hydrothermal, solvothermal, sol–gel synthesis and co-precipitation, facilitate the creation of nanomaterials with controlled sizes and shapes from the smallest atoms. In recent years, green synthesis has emerged as a sustainable and environmentally friendly technique, utilising biological entities like plants, microorganisms, algae and actinomycetes as precursors of reducing agents to produce metal nanomaterials, such as silver, copper and cerium. The chapter highlights the importance of nanomaterial processing techniques in determining the structural, optical, mechanical, electrical and magnetic properties of the resulting materials. Despite significant advancements, challenges persist in achieving precise control over nanomaterial properties and scaling up production for industrial applications. This chapter addresses the research gap by examining the latest advancements, methodologies and their impact on various fields. It highlights the pivotal role of nanomaterial processing in enabling innovative applications and overcoming existing limitations. The choice of synthesis technique is discussed in the context of desired properties, applications and environmental considerations.